Numerical simulation of the dynamic evolution of the friction interface of PTFE/45 steel friction pair. (28th August 2019) - Xie, Ting; Chen, Kun; Zhou, Zhenghua; Yang, Huaping
Abstract: The software of the Particle Flow Code in 2 Dimensions (PFC2D) was employed to simulate the dynamic evolution of the friction interface of the PTFE/45 steel friction pair. The simulation results showed that the PTFE material near the friction interface can be divided into three different layers: (1) the transfer particle layer; (2) the quasi-fluid layer; and (3) the elastic-plastic deformation layer. The direction of the horizontal component force applied on the PTFE particles within the quasi-fluid layer and elastic-plastic deformation layer kept consistent with the movement direction of the 45 steel. A 'non-contact area' was formed at the moving front of the PTFE surface, and the area size was affected by applied load and sliding speed. The higher the load is, the shorter the 'non-contact area' is; the greater the speed is, the longer the 'non-contact area' is. The size of non-contact area has little effect on the number of transfer particles, but the worn particles decrease with the increase of 'non-contact area'. The simulation results are significant for optimizing material design and improving the friction performances.